Bacteriological and Antibiotic Susceptibility Profile of Uropathogens from a Tertiary Care Hospital - Balaji, Vignesh Kanna; PV, Anto; Indernath, Sunil (Journal of Neonatal Surgery, 2025)
Introduction: The resistance patterns varies significantly in different geographical area. Therefore, routine surveillance is mandatory for constant monitoring of AMR rates among the important pathogens. It is imperative to monitor the changing pattern over time to follow proper therapeutic strategies to control infections due to drug resistant pathogens. Aim: The aim of this study is to highlight the distribution of various organisms isolated from urine samples, and their susceptibility to different antibiotics collected during 2019 (July to December) in a tertiary care hospital. Materials And Methods: From 600 urine sample which were received in the microbiology department during the study period, culture was done and organism identification was done using standard conventional biochemical tests and antibiotic susceptibility was carried out according to CLSI guidelines on each of the culture isolates from urine sample. Conclusion: This study concluded that the majority of the urine samples grew bacteria and few samples grew fungi. E. coli was the predominant isolate among them. Gram negative bacteria were more commonly associated with UTI than gram positive organisms. A high level of resistance was seen among the most of the isolates.